Heparin-induced Thrombocytopenia: Yet Another Treatment Paradox? - Warkentin, Theodore E. (Thrombosis and Haemostasis, 2001)
Few topics in medicine rival heparin-induced thrombocytopenia (HIT) for the unexpected twists and turns enough to rival the plot of many a mystery novel. The underlying theme- anticoagulant-induced thrombosis- seems improbable, but is well-established: despite thrombocytopenia, patients rarely bleed spontaneously or even exhibit petechiae (1); rather, thrombosis develops in 30-75% of patients with HIT, depending upon the clinical situation, and in proportions far greater than expected based on the original reason for receiving heparin (2-4).But even beyond this fundamental contradiction, there exists for the unwary and uninformed practitioner several counterintuitive treatment paradoxes. One is the dichotomous nature of low-molecular-weight heparin (LMWH) respecting prevention and treatment of HIT. LMWH is far less likely to cause HIT than standard, unfractionated heparin (4, 5). Yet, for the patient with acute HIT caused by unfractionated heparin, LMWH is contraindicated (6, 7). The reason: LMWH preparations contain some heparin molecules with 12 or greater saccharide units, which are sufficiently long to bind platelet factor 4 (PF4), creating the multimolecular complexes bearing the HIT antigens. Consequently, ongoing platelet activation, thrombocytopenia, and thrombosis occur in many patients so treated (8).